Physicochemical, Sensory, and Microbiological Properties of Butterfly Pea Flower (Clitoria ternatea L.) Kombucha: Effects of Sugar Type and Starter Concentration - Haryanto Adhiwono, Enrico Valent; Nurdyansyah, Fafa; Umiyati, Rini; Ferdiansyah, M. Khoiron (Jurnal Pangan dan Agroindustri, 2026)
Butterfly pea flower (Clitoria ternatea L.) is a promising substrate for functional kombucha because of its anthocyanin and phenolic contents. This study evaluated the effects of sucrose and palm sugar combined with starter concentrations of 2, 4, and 6% (v/v) on physicochemical, antioxidant, sensory, and microbiological properties after 7 days of fermentation at 25–27 °C. A completely randomized factorial design with three replications was applied. The beverages had pH values of 3.32–3.74 and lactic acid bacteria counts of 6.44–8.41 log CFU/mL. The formulation containing 10% palm sugar and 4% starter produced the highest total phenolic content (52.22 mg GAE/mL), while 10% sucrose and 6% starter resulted in the strongest DPPH radical-scavenging activity (70.39%). The highest bacterial count was obtained with 10% palm sugar and 6% starter. Overall, palm sugar favored phenolic retention and microbial viability, whereas sucrose at 6% starter promoted antioxidant activity.